A Novel Mechanical Flux Weakening Method for Flux Switching Permanent Magnet Machine - Al-ani, Mahir; Oner, Yasemin (TAYLOR & FRANCIS INC, 2021)
This article presents a novel mechanical field weakening method for flux switching permanent magnet (FSPM) machines to extend the torque-speed characteristic and improve the efficiency at high speeds. The proposed method consists of segmenting the permanent magnets (PMs) part along the back-iron radius into a circular shape embedded into the rectangular magnet. The circular-shaped magnet segments (CMSs) can then be rotated to enhance or short circuit the PMs flux. When the magnetization orientation of the PMs and the CMSs are in the same direction, the flux will flow as of that of the conventional FSPM machine, i.e. field strengthen. Conversely, when the high speed is required, the CMSs will be rotated 180 degrees, and therefore, the PMs and the CMSs magnetization orientation will be in opposite direction, and therefore, a short circuit of the PMs flux will be created. This will lead to lower PMs flux linkage, and therefore, higher field weakening factor. A FSPM machine with 12/10 stator/rotor pole combination has been selected to investigate the proposed method. First, to study the proposed method, a comparison of the electromagnetic performance of the FSPM machine in flux strengthening and weakening states has been conducted and presented. Then, mechanical analysis of the proposed method has been made with focus on the mechanical rotating system and the consequent structural stress on the rotating magnet. In conclusion, the proposed method shown a good field weakening capability and improved torque-speed characteristics.
Keywords: flux switching; permanent magnet; field weakening; mechanical field weakening; flux enhanced; lumped parameter; rotated magnet; efficiency map; mechanical design; novel method; ELECTROMAGNETIC PERFORMANCE; Engineering